Holding therapy in Britain: historical background, recent events, and ethical concerns. (July 2013) - Mercer, Jean
Holding therapy, an intervention often used in the treatment of foster and adopted children, has been rejected by professional groups on grounds of lack of evidentiary support and of potential harmfulness. Nevertheless, some British proponents have continued to advocate its use. Is this support brought about by the familiarity of concepts used in this treatment? This article reviews the history of related concepts and methods in Britain. It is concluded that a long history of British involvement with related ideas may have encouraged approval of holding therapy, but that ethical concerns argue against its use.